Safety and efficacy of tranexamic acid in paediatric cardiac surgery: study protocol for a double-blind randomised controlled trial - Yang Wang; Xu Wang; Rong Wang; Yu Zhang; Zhe Zhang; Yuan Jia; Jia Shi; Su Yuan; Jinping Liu; Jun Ran; Yuchen Zhao; Zhongdong Hua; et al. (BMJ Open)
Introduction An initial retrospective study suggested that tranexamic acid (TXA) administration increased the incidence of seizures in paediatric patients undergoing cardiac surgery. However, the efficacy of TXA in paediatric cardiac surgery remains unclear owing to the small sample sizes of the studies. Therefore, this study will investigate the efficacy and safety of TXA in paediatric patients undergoing cardiac surgery. We hypothesised that TXA may increase the incidence of postoperative seizures with no effect on postoperative allogeneic transfusion in paediatric patients undergoing cardiac surgery. The pragmatic study will provide important implications for paediatric cardiac surgery.Methods and analysis This will be a single-centre prospective, double-blind randomised controlled trial. The plan is to enrol in the study 2090 paediatric patients aged 31 days to 7 years who will be undergoing cardiac surgery with cardiopulmonary bypass (CPB). All eligible participants will be randomly assigned to either the TXA or placebo group by using a Web-based randomisation service in a 1:1 ratio. The primary safety end point will be postoperative seizures until hospital discharge, and the primary efficacy end point will be the volume of allogeneic red blood cell transfusion after termination of CPB. All patients will be followed up for 1 year postdischarge. All data will be analysed in accordance with the intention-to-treat principle.Ethics and dissemination This study was approved by the institutional review board of Fuwai Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College (No 20191195). Written informed consent will be obtained from the parents/legal guardian of each patient because all participants will be <18 years of age. The results of the trial will be published in an international peer-reviewed journal.Trial registration number Chinese Clinical Trial Register (ChiCTR1900024131).